PENILAIAN KESTABILAN LERENG BATUGAMPING PADA KAMPUS LAPANGAN PPSDM GEOMINERBA - Meda Rusdiana Ipmawati (PPSDM Geominerba, 2019)
The condition of rock mass in nature is influenced by exogenous and endogenous forces, one of the consequences is the existence of a structure of discontinuity in rock mass, which is a rock mass increment which in the concept of stability may be a factor to reduce stability. In more detail, differences in surface roughness of the discontinuous plane (in this study are joint) and joint length (persistence) are properties that cannot be ignored in the assessment of slope stability conditions. Int his study, persistence was grouped into two, namely persistence of more than 3 m and persistence of less than 3 m. The measurement results obtained Joint Roughness Coefficient (JRC) which is a quantification of the roughness at the joint major (persistence more than 3 m) is at a value of 4-6 (as much as 71.4% of the total joints measured) and the rest is 0-2,2 -4, 8-10, and 12-14 based on the Barton-Bandhis scale (1977). In the stability analysis, the roughness of the major discontinuous plane is depicted under the actual conditions recorded in the cross section, while the minor joint (persistence less than 3 m) is described as a joint network with JRC values of combinations 4 and 8. The result, the slope condition of the study is considered safe based on six cross section analyzed. The smallest Strength Reduction Factor (SRF) value is at 1.89 and the probability of failure is at 5.81%, both of which are still within the safe range based on ministerial decree of Ministry of Energy and Mineral Resources No. 1827/2018.